PEMANFAATAN LAHAN BEKAS PEMBUANGAN SAMPAH MENJADI KEBUN SEHAT DI KELURAHAN RABANGODU UTARA - Hidayat, Andre; Ramadhan, M. Ajihir; Amalia, Rista Talitha; Mawar, Mawar; Qomah, Isti; Hamdani, Feri; Fajar, Nisrina Qatrunnada; Said, Abdul; Supraydi, Didy Ika (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) is a special program held by a University and used as a forum for students to serve a village or region through programs designed based on field surveys. Slum areas have become commonplace in Indonesia, especially areas that have received less attention from the government. This is due to the lack of public awareness of cleanliness, so they are indifferent to littering. A similar thing happened in one of the RTs in Rabangodu Utara Village where the people used empty land as a garbage dump. The solution offered to overcome this problem is to process the former garbage dump into a healthy garden, in the form of planting vegetables. This activity is carried out in stages starting with cutting grass, lifting garbage, loosening the soil, then planting seeds. From these activities, it is hoped that the healthy garden will be beneficial to the community.